The provision of business advice to SMEs by external accountants. Issue 3 (7th March 2016) - Carey, Peter; Tanewski, George
Abstract : Purpose: – Business advisory services are an emerging service category for external accountants in the small and medium-sized enterprise (SME) environment. The purpose of this study is to investigate determinants of SME demand for business advice, drawing on the agency theory, relational marketing and resource-based literatures. Design/methodology/approach: – The study empirically tested theoretical predictions based on an Australia-wide survey of SMEs, in which 485 firms responded to a questionnaire. Findings: – The results show that the purchase of business advice is significantly and positively associated with the perceived competence of the external accountant, but significantly and negatively associated with length of the relationship. However, the authors observe a significant positive interaction between tenure of the relationship and competence. A unique contribution of this study is the development of the understanding of the combined role of the external accountant's competence and the tenure of the relationship. The findings indicate that SMEs require time to verify whether accountants have the competence to provide business advice, suggesting that information asymmetry and uncertainty is minimised only after SMEs have nurtured relationships with their external accountants, and after they have developed some confidence in the competence of their external accountants. At the same time, the negative association with tenure suggests that when accountants are not perceived as competent advisors, SMEs purchase less advice over time. Research limitations/implications: – The paper has important theoretical implications by augmenting agency theory, the relational marketing and the resource-based literature, and it clarifies which antecedent factors are important in explaining demand for business advisory services provided by accountants to their SME clients. In particular, the paper highlights the importance of the combined roles that the external accountant's competence and tenure play in the SME–accountant relationship, highlighting how these two factors can overcome credence issues and ex ante information problems. Practical implications: – The findings have practical implications for government initiatives targeting support to SMEs, as the findings identify small firms and firms planning to grow as likely to gain the greatest benefit from external advice and support. Originality/value: – This study adds to the limited literature and scant theoretical discussions on the emergence of business advisory services that accountants provide to their SME clients by drawing on several theories to explain the determinants of business advice.